217k views
5 votes
Please Please Please help !!

Please Please Please help !!-example-1
User Acrophobia
by
5.5k points

2 Answers

5 votes

Answer:

g(x) = x - 7

Explanation:

g(x) is the same as saying "y".

you need to move the y-intercept down 7 units, therefore putting the term - 7 into the expression.

User Raekkeri
by
5.3k points
4 votes

Answer:

g(x) = x-7

Explanation:

First find f(x)

f(x) is the function y =x

f(x) = x

g(x) = f(x) + C C < 0 moves it down

We want to move it down 7 units

g(x) = f(x) -7

g(x) = x-7

User Carlos Goce
by
5.2k points